Synthesis of 4-(Dimethylamino)quinazoline via Direct Amination of Quinazolin-4(3H)-one Using N,N-Dimethylformamide as a Nitrogen Source at Room Temperature - Chen, Xin; Yang, Qin; Zhou, Yirong; Deng, Zhihong; Mao, Xuechun; Peng, Yiyuan (Synthesis, 2015)
An efficient direct amination of quinazolin-4(3H)-ones using N,N-dimethylformamide as a nitrogen source is described that affords the corresponding 4-(dimethylamino)quinazolines in high yields. This transformation proceeds through efficient 4-toluenesulfonyl chloride mediated C–OH bond activation at room temperature.
Keywords: amination; quinazolin-4(3H)-one; 4-aminoquinazoline